Sachlicher Zwang und persönliche Bevormundung: Die liberale Kritik am Wohlfahrtsstaat in den Programmschriften von Milton und Rose Friedman - Fiehler, Fritz (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
Criticism of the welfare state formulated in political and economic essays of Milton and Rose Friedman, Capitalism and Freedom (1963), Free to Choose (1980), and Tyranny of Status Quo (1983) are important examples of the neoliberal campaign against the welfare state. The study presents them as an ideologically motivated reaction to social change: »Productive classes« become the minority in late capitalism. In addition, the study shows them as an ideological attempt, to interpret spheres between the state and the market in economic terms.